Rain forest - Hughes, David (Washington, D.C. : National Geographic Society Educational Services, 1988)
Showcases the rare beauty and rich variety of plant and animal life found in a Costa Rican rain forest. Also examines the impact of man's exploitation of the rain forest on this fragile ecosystem.
Keywords: Rain forest ecology -- Costa Rica; Man -- Influence of nature -- Costa Rica; Ecology